The Association Between Clinical Characteristics and Histopathology of Nasopharyngeal Carcinoma At Dr. Mohammad Hoesin General Hospital, In 2019-2020 - Argo Fauzan; Susilawati Susilawati; Veny Larasati (Biomedical Journal of Indonesia, 2022)
Introduction. Nasopharyngeal carcinoma is a cancer originating from the nasopharyngeal epithelium. Clinical characteristics such as age, gender, and risk factors are believed to influence the incidence of this cancer. Patients suffering from nasopharyngeal cancer may have certain clinical symptoms and provide certain histopathological features. Methods. The method used in this research were analytic observational with a cross sectional design using secondary data in the form of medical records from the Department of Anatomical Pathology section and the Central Medical Record section of RSUP Dr. Mohammad Hoesin Palembang as the research subject. Samples obtained 64 samples, then managed using the SPSS application. Results. The highest age group was 35-55 years old, which amounted to 44 people (68.8%). According to gender, the most common were males with 53 people (82,8%). According to clinical symptom, the most common were non-epistaxis with 33 people (51.6%). According to risk factors, the most were smokers with 36 people (56.3%).  According to histopathology, the most common features were differentiated non-keratinized squamous cell carcinoma with 40 people (62,5%). From the statistical test, it resulted that p > 0,05 for all variables (age, gender, clinical symptoms, and risk factors) that associated with histopathology of nasopharyngeal carcinoma. Conclusion. There was no significant association found between clinical characteristics and histopathology of nasopharyngeal carcinoma.